Perbedaan Konsumsi Pangan Ibu HamilAnemia dan Nonanemia di Puskesmas Tapung Hilir 1 - Dewi Anggriani Harahap; Nur Afrinis; M. Nizar Syarif Hamidi (Jurnal Kesehatan Komunitas, 2021)
Anemia in pregnant women occurs due to a lack of food consumption in pregnant women, especially iron consumption. Hemorrhage postpartum is the main cause of maternal death due to anemia in pregnancy. The purpose of this study was to determine the differences in food consumption among pregnant women who are anemic and non-anemic in the working area of ​​the Tapung Hilir 1 Public Health Center, Kampar Regency. This type of research is quantitative with a case-control design. The sample of this research consists of 30 non-anemic pregnant and 30 anemia pregnant. The research instrument used a questionnaire and a food recall form 2x24 hours. Data collection techniques used were interviews. 24-hour food recall data were obtained for 2 non-consecutive days. The results of the analysis of the average energy consumption (47.37 kcal), protein (78.43 gr), carbohydrate (44.93 g), and iron consumption (17.37 mg). Analysis using the Mann Whitney test found differences in energy consumption, carbohydrates, Fe (p = 0.000) in anemic and non-anemic pregnant women, and there was no difference in protein consumption (p = 0.344) in anemic and non-anemic pregnant women It is expected that pregnant women can increase food consumption that can prevent anemia in pregnancy such as consumption of animal protein, iron, and vitamin C.